(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s ((3eMeO Ydj baWGfs)
(3ChdgG (B:s
(3cJGH GdNeS, hgh HVe GdNGA hEScGf Gdeje(B...s
(3BNQgG (B:s
(3hCf GdhdGjI ajg ddMGce hLgGf(B... (3ChdgeG(B: (3ef bhI ceG CaJi Hg TjN eTGjNfG aj cTag(B... (3aj CeKGd Pdc hGddg GdYGde HMbGFb CMcGeg Je cJGH GdNeS, hjJHYg cJGH GdUhQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B373s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B378s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis